The relationship between lifestyle habits and obesity among students in the Eastern province of Saudi Arabia: using the Arab Teens Lifestyle (ATLS) questionnaire - Alexander Woodman; Margaret Coffey; Anna-Mary; Nizar Jaoua (BMC, 2024)
Abstract Background The Arab Teens Lifestyle (ATLS) questionnaire was an initiative to assess the lifestyle habits influencing obesity rates in the Middle East and North Africa (MENA) region, including physical activity (PA) patterns, sedentary and eating behaviours. Since its implementation, the ATLS questionnaire has been used in several studies among different age groups and populations. This instrument has not previously been administered among the university students of the Eastern Province of Saudi Arabia, where the obesity rates are the highest in the country. This research was the first that aimed to identify lifestyle habits influencing the rates of obesity among 18-25-year-old university students in the Eastern Province of the Kingdom of Saudi Arabia (KSA) using the ATLS questionnaire. Methods Quantitative cross-sectional research among n = 426 students of the Eastern Province of Saudi Arabia using the ATLS questionnaire. Results Out of n = 426 participants, n = 200 (47%) were categorised (using body mass index) as normal weight; n = 113 (26.5%) were overweight, and n = 73 (17.1%) were obese. The findings showed that most of the nutritional, PA, and sedentary behavioural factors (e.g., screen time) in the questionnaire were not associated with obesity status amongst the participants. In the obese group, more of the males that consumed fruits, French fries, cakes, sweets and doughnuts more than three times per week were likely to be obese, which was not the case for females. Conclusion The reported lifestyles of the students could potentially lead to long-term negative health effects, which is of concern given the rising rates of overweight, obesity, and obesity-related non-communicable diseases (NCDs) among the Kingdom's adult and ageing population. Further studies are recommended to explore the knowledge, attitudes, and perceptions of Saudi students in the Eastern Province in relation to PA, sedentary behaviours, and dietary habits, along with their views on how these can be improved.